Meningkatan Kemampuan Berpikir Kritis Siswa Kelas X Melalui Model Pembelajaran Problem Based Learning di SMK Pertukangan Santo Yusup - Yonas Yonas (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This Classroom Action Research (CAR) aims to improve the critical thinking skills of Grade X students at SMK Pertukangan Santo Yusup by applying the Problem-Based Learning (PBL) model. The background for this research is the previously low critical thinking skills of students, who tended to be passive and less actively involved in the learning process. The method used is Classroom Action Research (CAR) divided into two cycles, Cycle I and Cycle II, covering the stages of planning, implementation, observation, and reflection. In the first cycle, observation results showed that most students were still in the low category of critical thinking skills, with only a few reaching the